2014
DOI: 10.1007/s40477-014-0101-x
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler sonography to predict the risk of surgical recurrence of Crohn’s disease

Abstract: Purpose The aim of this work is to investigate the role of power Doppler sonography as an additional predictor of surgical recurrence in Crohn's disease. Methods A sample of 33 patients, with ileal or ileocolonic Crohn's disease, that had underwent intestinal resection, were retrospectively enrolled. All patients had bowel ultrasonography 7-16 months after resection. Power Doppler sonography of the preanastomotic ileum was evaluated as a possible prognostication tool to assess the risk of long-term need for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…High-frequency ultrasound of the bowel wall is used in patients with UC to reveal signs of inflammation such as bowel wall thickening, loss of wall stratification, or increased blood flow within the thickened wall (15,16). This inflammation may change elasticity of the bowel wall and might be depicted by ARFI point shear wave elastography.…”
Section: Discussionmentioning
confidence: 99%
“…High-frequency ultrasound of the bowel wall is used in patients with UC to reveal signs of inflammation such as bowel wall thickening, loss of wall stratification, or increased blood flow within the thickened wall (15,16). This inflammation may change elasticity of the bowel wall and might be depicted by ARFI point shear wave elastography.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bowel wall thickness, increased vascularization measured by Doppler signal or CEUS may be additional tools to predict POR [ 38 , 39 ]. An Italian group identified bowel wall thickness (cutoff value of bowel wall thickness > 3 mm) and power color Doppler at anastomosis assessed by IUS one year after surgery as predictors of early recurrence after ileo-colonic resection.…”
Section: Intestinal Bowel Ultrasound In Patients With Crohn’s Diseasementioning
confidence: 99%
“…In two recent studies we found that bowel wall thickness at the anastomosis >3 mm, detected through bowel ultrasound performed 1 year after surgery [3], with additional contribution of power-colour Doppler [4] could be added to the list of non-invasive predictors of early recurrence after ileo-colonic resection besides those already known in literature.…”
Section: Dear Editormentioning
confidence: 94%
“…The hypoechoic echopattern of bowel wall is associated with predominant acute inflammatory changes of bowel wall when compared to the stratified pattern [5], like a positive power Doppler [4].…”
Section: Dear Editormentioning
confidence: 96%